A Fluorinated Phenylene Unit as a Building Block for High‐Performance n‐Type Semiconducting Polymer. (22nd March 2013) - Park, Jung Ha; Jung, Eui Hyuk; Jung, Jae Woong; Jo, Won Ho
<x xml:space="preserve">Abstract</x> Copolymers composed of diketopyrrolopyrrole and phenylene units with different numbers of fluorine subsitution are synthesized. When the effect of the number of fluorine substitution on the n‐channel transporting property is investigated, the polymer with four fluorine substitutions exhibits the best n‐type charge‐transporting behavior with an electron mobility of 2.36 cm2 V−1 s1. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>